Effect of carbonisation temperature and activating agents on the characteristics of activated carbon produced from oil palm empty fruit bunch. Issue 1 (April 2021) - Hendrawan, Y; Nurseta, D Y; Utami, R; Daisy,; Trilaksana, M I A; Sumarlan, S H; Wibisono, Y
Abstract: This study aimed to analyse the effect of carbonisation temperature and type of activating agent which were best to be used in the chemical activation process in the manufacture of activated carbon from oil palm empty fruit bunches (EFB). The process of making activated carbon consisted of three stages, i.e. dehydration, carbonisation, and activation process. The experimental design was a randomised block design arranged as factorial with two factors, i.e. the first factor was variations of carbonisation temperature: 300°C, 400°C, and 500°C the second factor was the variations of activating agent type: ZnCl2, CaCl2, CH3 COOH, and without activation. The results showed that carbonisation temperature and the type of activating agent had a significant effect on the characteristics of the activated carbon. The best results were achieved using CH3 COOH as the activating agent at by the 500°C. The characteristics of the best-activated carbon consisted of 5.78% of ash content, 19.84% volatile matter content, 74.39% fixed carbon content, 1007.320 mg/g adsorption of iodine solution. The Brunauer – Emmett – Teller (BET) surface areas were up to 1110.87 m 2 /g and had a hollow surface structure, and open pores with a weight percentage atoms component of carbon reached 77.132%.